KEBIJAKAN DAN IMPLEMENTASI BANTUAN LUAR NEGERI AUSAID DI TIMOR LESTE: EVALUASI TERHADAP PROYEK DUKUNGAN RENCANA STRATEGIK SEKTOR KESEHATAN - Retna Siwi Padmawati, Manuela Pereira, Yodi Mahendradhata, (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: The Ministry of Health of Timor-Leste has realizedthat they should work together with other stakeholders toachieve their vision and mission due to insufficient humanresources and budget. Therefore, the Ministry of Health hasestablished collaboration with AusAid and other developmentpartners through mechanism of coordination. However, themechanism is not yet implemented fully.Objective: To evaluate foreign aid policy in coordinating AusAiddonor and development partners to fund human resource developmentprogram (in the HSSP-SP project) through the mechanismof coordination in the Ministry of Health of Timor-Leste.Method: This was a qualitative study with a case-study design.The respondents were 16 people, consisting of 13 personsfrom the Ministry of Health and 3 persons from AusAid,World Bank and development partners.Result and Discussion: The Department of Partnership Managementhad not been optimum in managing and controlling theproject/program and activities of the donors and working partners.The approved action plan and budget were relevantwith the proposal made by the Ministry of Health but planningfor human resource development was unclear and was notbased on the work force gap faced and priority in humanresource development. The project had impact on human resourcedevelopment but the process of staff re-placementwas not in line with the principle of the right man on the rightplace. Regular consultative meeting could facilitate the approvalof action plan and budget for human resource development.However, the mechanism of coordination was less effectivebecause there was no specific instrument or mechanismto do alignment and harmonization and it only focused oncollective gain and there was too much pressure and demandto staff from both the Ministry of Health and partners. Constraintsand challenges from political aspect and human resourcecapacity had hampered the process of coordinatingAusAid and working partners.Conclusion: The implementation of foreign aid policy to coordinateAusAid and development partners to fund human resourcedevelopment (in HSSP-SP project) following the mechanismof coordination in the Ministry of Health of Timor-Lestehad run well enough but still received lack of support fromhuman resource development planning based on institutionaldevelopment.Keywords: policy evaluation, mechanism of coordination,human resource development, donor agency